Species diversity, composition, and heterospecific associations of trees in three altitudinal gradients in Bird's Head Peninsula, Papua, Indonesia - Sepus Marten Fatem; Dony Aristone Djitmau; Antoni Ungirwalu; Alfredo Ottow Wanma; Victor Immanuel Simbiak; Nithanel Mikael Hendrik Benu; Junus Tambing; Agustinus Murdjoko (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fatem SM, Djitmau DA, Ungirwalu A, Wanma AO, Simbiak VI, Benu NMH, Tambing J, Murdjoko A. 2020. Species diversity, composition, and heterospecific associations of trees in three altitudinal gradients in Bird's Head Peninsula, Papua, Indonesia. Biodiversitas 21: 3596-3605.  The region of Bird's Head Peninsula, West Papua, Indonesia has a high level of vegetation diversity distributed from coastal to mountain areas. Yet, the information regarding this diversity is limited. We studied species diversity, composition, and heterospecific association of trees in three altitudinal gradients in Bird's Head Peninsula to reveal the biotic phenomenon in the region. Systematic random sampling was applied during data collection in three locations representing lower, middle, and upper altitudes of natural tropical forest. We applied diversity indices to investigate taxonomic diversity, importance value index (IVI) to reveal floristic composition and canonical correspondence analysis (CCA) for heterospecific associations. In total, we recorded 30 families, 44 genera, and 66 species in the three locations. There were 20 families in lower area and each 15 families in middle and upper areas while the genera per site were 29 in lower, 20 in the middle, and 18 in the upper. The number of species found in lower, middle, and upper areas was 35 species, 24 species, and 27 species respectively. The research revealed that the taxonomic diversity of trees generally decreases as the elevation increases in terms of family, genera, and species level. The dominant species was also different across elevation gradients in which the dominant tree had a different pattern in the three locations between understory and upperstory. Moreover, the gradient of elevation has shaped the type of tree communities, suggesting interactions and associations among tree species. Of all species recorded, 26 species were listed in IUCN Red List with two species were under data deficient, 20 species were least concern, three species were near threatened, and one species was vulnerable.